simplify (81/16)^-3/4 x { (25/9)^-3/2 divided by ( 5/2) ^ -3
plz show the method
Answers
Answered by
0
(81/16)^-3/4 × { (25/9)^-3/2 ÷ (5/2)^-3}
=. (3/2)^4×-3/4 × {(5/3)^2×-3/2 ÷ (5/2)^-3}
=. (3/2)^-3 × {(5/3)^-3 ÷ (5/2)^-3}
Now to make power positive reciprocate the fractions.
(2/3)^3 × {(3/5)^3 ÷ (2/5)^3}
(2/3)^3 × {(3/5)^3 × (5/2)^3}
(2/3)^3. × (3/2)^3
(1)^3
= 1
Thanks
=. (3/2)^4×-3/4 × {(5/3)^2×-3/2 ÷ (5/2)^-3}
=. (3/2)^-3 × {(5/3)^-3 ÷ (5/2)^-3}
Now to make power positive reciprocate the fractions.
(2/3)^3 × {(3/5)^3 ÷ (2/5)^3}
(2/3)^3 × {(3/5)^3 × (5/2)^3}
(2/3)^3. × (3/2)^3
(1)^3
= 1
Thanks
Answered by
0
Step-by-step explanation:
For any two real numbers a and b, a, b ≠ 0, and for any two positive integers, m and n
➲ If a be any non - zero rational number, then
a^0 = 1
➲ If a be any non - zero rational number and m,n be integer, then
(a^m)^n = a^mn
➲ If a be any non - zero rational number and m be any positive integer, then
a^-m = 1/a^m
➲ If a/b is a rational number and m is a positive integer, then
(a/b)^m = a^m/b^m
➲ For any Integers m and n and any rational number a, a ≠ 0
a^m × a^n = a^m+n
➲ For any Integers m and n for non - zero rational number a,
a^m ÷ a^n = a^m-n
➲ If a and b are non - zero rational numbers and m is any integer, then
(a+b)^m = a^m × b^m
I hope it's help you...☺
:)
Similar questions